The effect of epinephrine for the treatment of spinal-hypotension: comparison with norepinephrine and phenylephrine, clinical trial - Biricik,Ebru (2020)
Abstract Background and objectives: Limited data are present on safety and efficiency of epinephrine for the prophylaxis and treatment of spinal-hypotension. This study was conducted to compare the effect of epinephrine with norepinephrine and phenylephrine on the treatment of spinal-hypotension and ephedrine requirement during cesarean delivery. Methods: One hundred and sixty parturients with uncomplicated pregnancies undergoing elective cesarean delivery under spinal anesthesia were recruited. They were allocated randomly to receive norepinephrine 5 µg.mL−1 (n = 40), epinephrine 5 µg.mL−1 (n = 40), phenylephrine 100 µg.mL−1 (n = 40) or 0.9% saline infusions (n = 40) immediately after induction of spinal anesthesia. Whenever systolic blood pressure drops to less than 80% of baseline, 5 mg of intravenous ephedrine was administered as rescue vasopressor. The incidence of hypotension, total number of hypotension episodes, the number of patients requiring ephedrine, the mean amount of ephedrine consumption and side effects were recorded. Results: There was no statistically significant difference in incidence of maternal hypotension between groups. The number of patients requiring ephedrine was significantly greater in group saline than in group phenylephrine (p< 0.001). However, it was similar between phenylephrine, norepinephrine, and epinephrine groups. The mean ephedrine consumption was significantly higher in group saline than in norepinephrine, epinephrine, phenylephrine groups (p= 0.001). Conclusion: There is no statistically significant difference in incidence of hypotension and ephedrine consumption during spinal anesthesia for cesarean delivery with the use of epinephrine when compared to norepinephrine or phenylephrine. Epinephrine can be considered an alternative agent for management of spinal hypotension.